Estimating Job Satisfaction and Commitment Correlate of Senior Staff Members of the University for Development Studies, Tamale, Ghana - Abdallah, Yussif; Alhassan, Ibrahim (European Journal of Human Resource, 2021)
Purpose: Employees' Job Satisfaction (JS) is becoming an important asset to an organisation, especially in the recent past. All other things being equal, satisfied employees are likely to be more productive as a result of citizenship and/or loyalty, decreased-absenteeism, high-commitment and so on. With the knowledge that a positive relationship may exist between employees JS and their commitment, it becomes imperative that management of universities institute measures to regularly collect data on employees' JS. Thus, this study examined Senior Staff (SS) JS and their commitment relationship in the University for Development Studies (UDS), Tamale. Methodology: A structured questionnaire was administered to 231 Senior Staff (SS) members of the University. Of this number, which was determined using the Taro Yamane's formula for sample size determination, valid data retrieved and analysed represented a response rate of 92 per cent (212). Whilst the study employs One-Way ANOVA to compare the JS and the commitment level among the SS employee group to the University, Correlation and Regression Analyses were performed to establish associations and to determine the cause-effect relationship between the two variables. Findings: The results of the study indicated that 74 per cent of SS commitment is influenced by their satisfaction level. Thus, the study concluded that the management of the University should priorities staff JS in almost all its corporate decisions, as this will engender their commitment to the University. Unique Contribution to Practice and Policy: Organisational Commitment (OC) with all its dimensions (affective, continuance and normative) were confirmed to have a positive relationship with the JS of SS of a multi-campus public university; suggesting that OC does not only predicts JS in terms of teaching staff, as indicated by previous studies, but it also does so even with SS (who are in the non-teaching category). It was, therefore, recommend, based on the findings of this study, that the management of the UDS should priorities staff JS in almost all its corporate decisions, as this will engender their commitment to the University.